2014
DOI: 10.1136/jnnp-2014-308813
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1, CGRP and SP in scalp arteries of patients suffering from chronic migraine

Abstract: This study yields the first evidence for the existence of a TRPV1-LI innervation in human scalp arteries and provides the first quantitative assessment of the TRPV1-LI, CGRP-LI and SP-LI innervation of those vessels. The increase of TRPV1-LI periarterial nociceptive fibres of scalp arteries may represent, at least in some participants, a structural condition favouring CM (and possibly migraine), for example, by causing a higher sensitivity to algogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…In accordance with this, clinical findings report that TRPV1 receptor plays a role in pain and hyperalgesia associated with inflammation, injury, acidosis and cancer (Holzer, 2008). As regards the trigeminal system, a positive correlation between TRPV1-LI sensory afferents and pain score has been shown in dental pain (Morgan et al 2005) and chronic burning mouth syndrome (Yilmaz et al 2007), and we detected an increased density of the TRPV1-LI vascular innervation of scalp arteries in chronic migraine (Del Fiacco et al 2015). The percentage of the TRPV1-positive neurons we detected in the adult TG is double the percentage that was previously reported by Hou et al (2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with this, clinical findings report that TRPV1 receptor plays a role in pain and hyperalgesia associated with inflammation, injury, acidosis and cancer (Holzer, 2008). As regards the trigeminal system, a positive correlation between TRPV1-LI sensory afferents and pain score has been shown in dental pain (Morgan et al 2005) and chronic burning mouth syndrome (Yilmaz et al 2007), and we detected an increased density of the TRPV1-LI vascular innervation of scalp arteries in chronic migraine (Del Fiacco et al 2015). The percentage of the TRPV1-positive neurons we detected in the adult TG is double the percentage that was previously reported by Hou et al (2002).…”
Section: Discussionsupporting
confidence: 90%
“…This warns against the extrapolation of data obtained from experimental animals and requires the acquisition of specific knowledge of human regional chemical neuroanatomy. Regarding the localization of the TRPV1 receptor in the human trigeminal somatosensory system, the available information pertains, to the best of our knowledge, to the TG neurons (Hou et al 2002) and to certain territories of their peripheral innervation (Morgan et al 2005;Yilmaz et al 2007;Del Fiacco et al 2015). With a view to contributing to the characterization of the capsaicin-sensitive component of the human trigeminal sensory system, we present new data here concerning the immunohistochemical occurrence of the TRPV1 receptor in autoptic specimens of the human TG and spinal trigeminal nucleus, and we compare this with that of CGRP and SP.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, increased TRPV1, CGRP, and SP expression levels are correlated with patients suffering from chronic migraines. 42,43 TRPV1 antagonists have also been evaluated in the treatment of this disorder 44 . Of direct relevance to our research, a significant percentage of military veterans with blast-related injuries and confirmed TBI have also been diagnosed with migraine headaches and/or chronic, daily headaches 45 .…”
Section: Discussionmentioning
confidence: 98%
“…''TRPA1 is emerging as a major contributing pathway in migraine'' and ''TRPA1 is also implicated in the pathogenesis of asthma'' (Benemei et al, 2014(Benemei et al, , p. 2552Deering-Rice et al, 2015, p. 893). TRPV1-like immunoreactive innervention was increased in the scalp arteries of migraineurs, and TRPV1 expression was increased in nasal mucosa in idiopathic rhinitis (Del Fiacco et al, 2015;Van Gerven et al, 2014). In some children with asthma, gene polymorphisms for TRPA1 were associated with reduced asthma control (Deering-Rice et al, 2015).…”
Section: Trpa1 and Trpv1mentioning
confidence: 99%